Sistem Informasi Penjadwalan dan Agenda Kegiatan Bagian Kesejahteraan Masyarakat - Siti Kania Thisara; Raissa Amanda Putri (Jurnal Ilmu Komputer dan Sistem Informasi, 2026)
The rapid development of information technology has encouraged government institutions to improve efficiency in managing administrative and operational activities. The Community Welfare Section (Kesra) of the Governor’s Office of North Sumatra still faces difficulties in managing schedules and agendas due to manual recording processes. This often leads to overlapping schedules, delayed information delivery, and poor record management. This study aims to design and develop a web-based scheduling and agenda information system to support more effective and integrated administration. The Waterfall software development method was applied, consisting of requirement analysis, system design, implementation, testing, and maintenance stages. The system was developed using PHP programming language and MySQL database. Testing using the black-box method showed that all system functions operate properly, including agenda management, activity archiving, and notification features. The implementation of this system reduces scheduling errors, accelerates information delivery, and supports decision-making based on well-documented data.